Deep well new data in the area of the 2022 Mw 5.5 earthquake, Adriatic Sea, Italy: In situ stress state and P-velocities - Montone, Paola; Mariucci, Maria Teresa (Frontiers in Earth Science, 2023)
Following the Mw 5.5 earthquake of 9 November 2022 that occurred along the Adriatic coast of Italy and the related seismic sequence, we analysed new data from deep wells drilled in recent years by ENI S.p.A. Specifically, we calculated the horizontal stress orientations from breakouts recognized in three wellbores, determined the P-wave velocities for the first 5 km of crust from 12 well sonic records, and then calculated the vertical stress values in the area. Our results, indicating orientations of the present-day stress field of ~N130 and ~N040 for minimum and maximum horizontal stress, respectively, are consistent with the seismic sequence focal solutions. Thrust faulting focal solutions occurring at a hypocentral depth between 5 and 10 km, show minimum horizontal stress oriented at ~N140, which is also in agreement with the compressive tectonics of the area and the known seismogenic sources. The crustal P-wave velocities vary as a function of both the lithology crossed and the geological-structural location of the wells, suggesting several velocity patterns in a confined area. The average vertical stress for the investigated area, inferred from the velocity-derived density, shows values of ~100 MPa at a depth of 4.5 km, with a gradient varying from 21 to 23 MPa/km. The obtained in situ stress measurements indicate that no stress regime changes or temporal rotations have been observed in the past 50 years throughout the entire area. The new stress indicators fill a geographical gap between the northern and southernmost existing data coherently with a compressive stress regime.